Early sexual initiation in Europe and its relationship with legislative change: A systematic review - Zhu, Guangxing (International journal of law, crime and justice, 2019)
Early sexual initiation is often considered risky behaviour as it is related with adverse consequences such as sexually transmitted diseases or unwanted pregnancy. Multiple academic studies have demonstrated that in the second half of the 20th century, the age of young people's first sexual initiation was on the decline in developed countries. However, little research has been conducted on the situation in the 21st century. By systematically reviewing recent studies on the timing of persons' first sexual initiation in European countries, this article revealed the latest trends in the age of first sexual initiation in Europe: 1) the continuing decline of age of first sexual initiation, and 2) the difference in timing of first sexual initiation between males and females. These two findings were then compared with the latest trends in age of consent legislation in Europe to see the relationship between the trends of age of sexual initiation in law and in practice.